Branding effects on small and medium sized enterprises performance in Malaysia: a conceptual framework - Tock, Jing Mi (American Scientific Publishers, 2015)
Small to medium sized enterprises is growing tremendously in Malaysia and has great potential to improve in terms of performance by utilizing the resources meritoriously and implementing the right strategy. The businesses in Malaysia are still struggling with branding even though there are commercial establishments in the SME category. Realizing the importance of branding, firms in this country need to strengthen branding implementation to be in a better position to build strong brands because businesses here are in general lack of branding appreciation and suffer from branding misconceptions. Hence, this study proposes an empirical study to examine the relationship between branding involving different dimensions such as brand trust, orientation and brand equity in affecting SMEs in Malaysia. The aim of this article is gather and review the growing visibility of these branding dimensions notions among firms from different studies, social theorists and author’s perspectives to conceptualize into a framework that responds to the performance of SME. It is considered the first research that measures the branding among SMEs in Malaysia and its impact to the performance of the smaller firms in Malaysia. The insights from this research may implicate other emerging markets with similar situations and further creates an understanding of the subject matter.